Conceptions of Geography Teachers on Student Perceptions and how to Deal with them in Teaching Practice - Barthmann, Kati; Conrad, Dominik; Obermaier, Gabriele (Journal of Geography Education, 2019)
This study primarily aimed at capturing ideas of Geography teachers about students' conceptions. Its second objective was to gain insight into the handling of students' conceptions in teaching practice. In an exploratory study, we interviewed 17 Geography teachers from Bavarian lower and upper secondary schools. The model of general action competence according to Baumert and Kunter (2006) formed the theoretical framework of this study. Qualitative content analysis served to analyze data. The results show–among others–that teachers have developed theory-like ideas about students' conceptions mainly of their professional experience and less on the grounds of their professional knowledge. The study thus links research in Geography education with school practice.
Keywords: teachers‘ beliefs, teacher professionalization, teacher expertise, students‘ conceptions, conceptual change